Quercetin-loaded nanoparticles enhance cytotoxicity and antioxidant activity on C6 glioma cells - Ersoz, Melike; Erdemir, Aysegul; Derman, Serap; Arasoglu, Tulin; Mansuroglu, Banu (TAYLOR & FRANCIS LTD, 2020)
Quercetin (Qu) is a natural flavonoid present in many commonly consumed food items. The dietary phytochemical quercetin prevents tumor proliferation and is a potent therapeutic cancer agent. The purpose of this study was to synthesize and characterize quercetin-loaded poly(lactic-co-glycolic acid) nanoparticles (Qu(1)NP, Qu(2)NP, and Qu(3)NP) with different size and encapsulation properties and to evaluate their in vitro activity on C6 glioma cells. Nanoparticles were synthesized by single emulsion solvent evaporation method. Then, particle size, zeta potential, polydispersity index and encapsulation efficiency of nanoparticles were determined. Particle size of Qu(1)NP, Qu(2)NP, and Qu(3)NPs were determined as 215.2 +/- 6.2, 282.3 +/- 7.9, and 584.5 +/- 15.2 nm respectively. Treating C6 glioma cells with all nanoparticle formulations effectively inhibited the cell proliferation. Qu(1)NPs were showed the lowest IC50 value in 48 h with 29.9 mu g/ml and achieved higher cellular uptake among other nanoparticles and Qu. Additionally, 48-h treatment with Qu(1)NPs significantly decreased MDA level (14.90 nmol/mu g protein) on C6 glioma cells which is related to reduced oxidative stress in cells. Findings of this study revealed that quercetin's cellular uptake and anti-oxidant activity is improved by small-sized Qu(1)NPs in C6 glioma cells.
Keywords: Quercetin; nanoparticle; PLGA; cytotoxicity; antioxidant activity; C6 glioma; PLGA NANOPARTICLES; DRUG-DELIVERY; BIODEGRADABLE NANOPARTICLES; CANCER; APOPTOSIS; Pharmacology & Pharmacy